CCNP 2.0 building Cisco scalable networks - Rossi, Lou (Certification / Networking)
This set of computer optical disks provide basic navigational control for learning purposes. It includes course notes, pre course test to assess user's skill, post - course test to help you mastering new skills and the test results. You may also search via keywords. Guide you in preparation for Cisco Routing Exam 640 - 503. After completing the lessons you will be able to address network managers and administrators task, managing access and controlling overhead traffic in growing, routed and networks.